2022
DOI: 10.1136/bmjopen-2021-058075
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biodegradable and durable polymer drug-eluting stents in acute coronary syndrome: a meta-analysis

Abstract: ObjectiveTo compare the safety and effectiveness between biodegradable polymer drug-eluting stents (BP-DES) and durable polymer drug-eluting stents (DP-DES) in patients with acute coronary syndrome (ACS).DesignMeta-analysis of randomised controlled trials (RCTs).Primary and secondary outcome measuresMajor adverse cardiovascular events (MACEs) were considered the primary endpoint. Efficacy endpoints included target vessel revascularisation (TVR) and target lesion revascularisation (TLR). Safety endpoints includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…DES with biodegradable polymers have been shown to improve device‐ and patient‐oriented clinical outcomes up to 5 years of follow‐up compared to BMS and early‐generation polymer‐based DES 20,21 . A meta‐analysis comparing biodegradable polymer DES with durable polymer DES concluded, that biodegradable polymer DES might be more favorable when treating patients with ACS 9,22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DES with biodegradable polymers have been shown to improve device‐ and patient‐oriented clinical outcomes up to 5 years of follow‐up compared to BMS and early‐generation polymer‐based DES 20,21 . A meta‐analysis comparing biodegradable polymer DES with durable polymer DES concluded, that biodegradable polymer DES might be more favorable when treating patients with ACS 9,22 …”
Section: Discussionmentioning
confidence: 99%
“…8 To improve safety of DES and decrease risk of inflammation due to durable polymers, DES with a biodegradable polymer (BP-DES) were designed, and meta-analysis shows that these BP-DES are significantly more effective than bare metal stents (BMS) and safer than first-generation DES. 9,10 Theoretically, BP-DES would decrease risk of inflammation and late stent thrombosis (LST), since it leaves behind a BMS after complete drug elution and polymer degradation. However, long-term follow-up studies are needed to assess the safety of newer stents.…”
Section: Introductionmentioning
confidence: 99%
“…In most stent trials, there is no evidence of an interaction between patient subgroups and the efficacy of one type of stent compared with another. A biodegradable polymer DES may be more suitable for patients with stent thrombosis myocardial infarction [56]. The BIOSTEMI trial demonstrated the superiority of the ultrathin sirolimus-eluting bioresorbable polymer stent Orsiro over the durable polymer everolimus-eluting XIENCE at one year based on TLF [57].…”
Section: Patient-specific Stentsmentioning
confidence: 99%
“…ACS has a poor prognosis and a high mortality rate among cardiology diseases. Currently, most patients with ACS are treated with percutaneous coronary intervention (PCI) [ 4 ]. The main application of this method is cardiac catheterization technology, which can make the narrowed or occluded coronary artery lumen reopen and improve the quality of the coronary artery [ 5 ].…”
Section: Introductionmentioning
confidence: 99%